Does Economic Freedom Moderate Perceived Corruption for Firms in India? - Nabamita Dutta; Saibal Kar; Adam Stivers (Institute of Labor Economics (IZA), 2023)
Available wisdom suggests that a negative relationship prevails between economic freedom and perceived corruption among firms. However, the relationship is far from linear and a number of complex interactions make it fairly nuanced. We show that greater competition may accentuate the problem of corruption. This is contrary to the general observation that regulations create conditions for corrupt practices. This study uses a broad-based survey for India to examine the role of economic freedom in influencing perceived corruption. The firm-level data helps to explore the relationship between economic freedom across Indian states and the perceived corruption in the formal sector. A statistically significant negative relationship as we obtain implies a fall in perceived corruption as a function of rise in contemporaneous and lagged economic freedom. These results hold when we design matching models and add a number of covariates with potentially opposite impact overall. The empirical structure clearly highlights the process of identification and shows that small and young firms and those with sole ownership perceive greater benefits from higher economic freedom. However as claimed above, older firms perceive higher corruption when economic freedom is higher. This lends support to the idea that competition facilitated by economic freedom can increase rent seeking behavior. Our study contributes to the literature by emphasizing that the relationship between economic freedom and corruption in India is layered, with firm characteristics playing a crucial role.
Keywords: D73; E26; J54; L11; P37; 330; perceived corruption; economic freedom; firm size; ownership; India